Nurses Knowledge Assessment Concerning Prevention of Ventilator-Associated Pneumonia (Medico Legal Update, 2020)
(VAP) is defined as pneumonia that develops in mechanically ventilated patients after 48 hours or more ofmechanical ventilator support, VAP increases the mortality and morbidity rates of patients and healthcarecosts, This study was a descriptive cross-sectional survey. Sample a total sample of 126 nurses was collectedfor the current study,setting and Participants a convenience sample of graduate nurses was obtained fromeight hospitals throughout Babylon. The study was approved by the ethics committees of the Babylon healthdepartment and the participating, Researcher used standard a questionnaire that integrated the assessment ofnurse’s knowledge for prevention of VAP from the Center of Disease Control and Prevention questionnairewas validated by a panel of four specialists in the disciplines of nursing, The questionnaire was administeredto the participants in their hospitals by the principle investigator. Nurses were informed that their completionof the questionnaire would be considered as consent to participate.SPSS version 22 was used for dataanalysis, The study conclude that the mean age of participants in the study was young and female, themajority of the nurses didn’t know that the mechanical ventilator humidifier must be changed weekly toprevent VAP. Researcher encourage all Iraqihospitals ICUs nurses to involve inclinical training to improvenurses acquisition and to evaluate the content of the nursing curricula to identify shortcomings in content.It is imperative that VAP-prevention guidelines be integrated in training and teaching within the nursingschools, and that the content and teaching strategies of infection control courses are updated.